Índices de qualidade da água no sistema de captação de água da região amazônica (Brasil) - (:unkn) unknown (Universidade Federal de Sergipe, 2019)
The lakes of Bolonha and Água Preta are used to supply part of the population of the Belém Metropolitan Region. This study aimed to evaluate water quality during a one-year period, by sampling five points distributed throughout the catchment system. The IQA average values classified the water quality as normal and the EIT averagevalues between eutrophic and supereutrophic. Despite the strong environmental impacts that occur in the catchment basin that suppliesthe BelémMetropolitan Region, it was observed that the capacity for self-purification and renewal was maintained. However, it is necessary for the responsible bodies, together with society, to continue to work to make it a viable water source. Environmental education actions for the population should be taken to promote environmental awareness, and mitigate the impacts caused by the advance of urbanization.
Keywords: Qualidade da água; Fósforo; Estado trófico; Utinga